RNA-FISH as a probe for heterogeneity at the cellular and subcellular levels in cyanobacteria - Mullineaux, Conrad W.; Wang, Kexin; Mahbub, Moontaha (Frontiers in Photobiology, 2024)
The abundance and subcellular location of specific mRNA molecules can give rich information on bacterial cell biology and gene expression at the single-cell level. We have been using RNA Fluorescent in situ Hybridization (RNA-FISH) to probe for specific mRNA species in both unicellular and filamentous cyanobacteria. We have shown that the technique can be used to reveal the locations of membrane protein production and can also reveal heterogeneity in gene expression at the single-cell level, including patterns of gene expression within the filaments of heterocyst-forming cyanobacteria as they differentiate in diazotrophic conditions. However, the background fluorescence from pigments in cyanobacteria can cause problems, as can the resistance of heterocysts to permeabilization. Here we discuss the potential and the pitfalls of RNA-FISH as applied to cyanobacteria. We compare the information that can be obtained from RNA-FISH with that available from other techniques for probing gene expression.